Social and demographic characteristics of Blue Duck Hymenolaimus malacorhynchos - Williams, Murray (Wildfowl, 1991)
A population of Blue Ducks inhabiting the Manganuiateao River in central North Island, New Zealand was studied over 1980-89. The birds were dispersed as pairs throughout the year with each pair occupying and defending territories which were similar in extent and location between years. Unpaired individuals also occupied territories throughout a breeding season. Pair associations persisted for up to 81 months (seven breeding seasons) and pair changes resulted mostly from challenges by bereaved neighbors. Only territorial pairs attempted breeding nests were in caves or amongst enveloping riverside vegetation within the territory and the same nest site was sometimes used in successive years. Mean egg size was 64.5 x 44.8 mm, mean clutch was 6.0, and eggs were laid at two-day intervals. Only the female incubated (for about 35 days) and 10% of nest failures were followed by a repeat laying. Both parents contributed parental care throughout the 70-80 day fledging period. Within the 9.3 km study area the number of territories occupied increased from four to ten over ten years. Fifty-eight breeding attempts produced 73 fledglings (mean 1.3 per breeding pair per year). Some individuals were more productive than others both in terms of the numbers fledged per breeding attempt and the numbers recruited into the breeding population. Annual survival of territory holders was 0.86, and that of juveniles in their 1st year 0.44. Recruitment into the breeding component of the population was 0.25 fledglings per breeding individual per year, twice that needed to replace lost adults. Productivity within the study area was higher than that on a neighboring and deeply incised 6.7 km section of the river in which territorial density also increased. Fledglings of both sex were highly philopatric, some establishing their territories immediately adjacent to their natal range. Nineteen of 26 birds which settled in the study area over the ten years were progeny of resident pairs and resulted in neighboring territory holders being closely related to each other. Two sibling pairings persisted through a breeding season and there were two other examples of direct inbreeding (adult-grandchild). The Blue Duck social system is similar to that of other southern hemisphere riverine ducks and it is argued that their population dynamics and structure will also exhibit striking similarities.